Uncovering transcriptional reprogramming during callus development in soybean: insights and implications - Park, Joo-Seok; Choi, Yoram; Jeong, Min-Gyun; Jeong, Yeong-Il; Han, Ji-Hyun; Choi, Hong-Kyu (Frontiers in Plant Science, 2023)
Callus, a valuable tool in plant genetic engineering, originates from dedifferentiated cells. While transcriptional reprogramming during callus formation has been extensively studied in Arabidopsis thaliana, our knowledge of this process in other species, such as Glycine max, remains limited. To bridge this gap, our study focused on conducting a time-series transcriptome analysis of soybean callus cultured for various durations (0, 1, 7, 14, 28, and 42 days) on a callus induction medium following wounding with the attempt of identifying genes that play key roles during callus formation. As the result, we detected a total of 27,639 alterations in gene expression during callus formation, which could be categorized into eight distinct clusters. Gene ontology analysis revealed that genes associated with hormones, cell wall modification, and cell cycle underwent transcriptional reprogramming throughout callus formation. Furthermore, by scrutinizing the expression patterns of genes related to hormones, cell cycle, cell wall, and transcription factors, we discovered that auxin, cytokinin, and brassinosteroid signaling pathways activate genes involved in both root and shoot meristem development during callus formation. In summary, our transcriptome analysis provides significant insights into the molecular mechanisms governing callus formation in soybean. The information obtained from this study contributes to a deeper understanding of this intricate process and paves the way for further investigation in the field.